2014
DOI: 10.3390/antibiotics3030450
|View full text |Cite
|
Sign up to set email alerts
|

A Point Prevalence Survey of Antibiotic Use in 18 Hospitals in Egypt

Abstract: Inappropriate antibiotic use leads to increased risk of antibiotic resistance and other adverse outcomes. The objectives of the study were to determine the prevalence and characteristics of antibiotic use in Egyptian hospitals to identify opportunities for quality improvement. A point prevalence survey was conducted in 18 hospitals in March 2011. A total of 3408 patients were included and 59% received at least one antibiotic, with the most significant use among persons <12 years and intensive care unit patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 8 publications
5
46
3
Order By: Relevance
“…The most commonly prescribed classes of antibiotics were third generation cephalosporins, imidazole derivatives and broad spectrum penicillins (Figure 3), consistent with a published study in Egypt [16]. The high prevalence of use of third generation cephalosporins in the pediatric ward ( Figure 3) could be attributed to the fact that pediatric patients tend to have a high prevalence of serious infections such as pneumonia and meningitis compared to adults.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The most commonly prescribed classes of antibiotics were third generation cephalosporins, imidazole derivatives and broad spectrum penicillins (Figure 3), consistent with a published study in Egypt [16]. The high prevalence of use of third generation cephalosporins in the pediatric ward ( Figure 3) could be attributed to the fact that pediatric patients tend to have a high prevalence of serious infections such as pneumonia and meningitis compared to adults.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies in Kenya have found a high prevalence of inpatient antibiotic use at 81.7% [14] and outpatient use at 68.0% to 72.9% of patients [14,15]. Among 18 hospitals in Egypt, the prevalence of antibiotic use was 59% among in-patients [16], and in Nigeria 55.9% of in-patients patients were prescribed antibiotics [8]. In China, the prevalence of antibiotic use among in-patients was 56% in a recent study [17].…”
Section: Introductionmentioning
confidence: 95%
“…The commonest indication for the prescription of our study antibiotics were respiratory infections just like the survey in 18 Egyptian hospitals. 16 Two other studies still found respiratory infections as predominant though at lower prevalence than that in present study. 4,14 As much as the current study population was restricted to those using the select antibiotics, the finding underpins the fact that respiratory infections are common in Kenya and may account for up to half of all hospital admissions in medical and pediatric wards.…”
Section: Discussioncontrasting
confidence: 67%
“…We have recently documented long periods of administration of antibiotics in surgical units in Ghana, at all levels of health facilities 9 . Long periods of administration of antibiotics have also been reported in other health facilities in low-and middle-income countries 22,23 .…”
Section: Discussionmentioning
confidence: 77%